2016
DOI: 10.1007/s13181-016-0562-8
|View full text |Cite
|
Sign up to set email alerts
|

Medical Toxicology and Public Health—Update on Research and Activities at the Centers for Disease Control and Prevention and the Agency for Toxic Substances and Disease Registry

Abstract: Evidence suggests that in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Higher consumption of non-traditional foods, as well as the more sedentary lifestyle that corresponds with movement away from traditional subsistence practices, has been linked to health problems such as obesity, diabetes, colorectal cancer, cardiovascular disease, and developmental disorders [65,70,76,77] and to nutritional deficiencies. For example, in the Yukon-Kuskokwim Delta of Alaska, a retrospective study of banked samples from young Alaska Native women taken from 1960 to 2010 showed a significant decline in plasma vitamin D concentrations associated with a drop in the consumption of traditional marine foods [78][79][80]. The prevalence of lifestyle-associated diseases has been increasing in remote communities throughout the circumpolar North.…”
Section: One Health In the Subsistence Contextmentioning
confidence: 99%
“…Higher consumption of non-traditional foods, as well as the more sedentary lifestyle that corresponds with movement away from traditional subsistence practices, has been linked to health problems such as obesity, diabetes, colorectal cancer, cardiovascular disease, and developmental disorders [65,70,76,77] and to nutritional deficiencies. For example, in the Yukon-Kuskokwim Delta of Alaska, a retrospective study of banked samples from young Alaska Native women taken from 1960 to 2010 showed a significant decline in plasma vitamin D concentrations associated with a drop in the consumption of traditional marine foods [78][79][80]. The prevalence of lifestyle-associated diseases has been increasing in remote communities throughout the circumpolar North.…”
Section: One Health In the Subsistence Contextmentioning
confidence: 99%
“…From 1998-2014, the Alaska Native Tribal Health Consortium, funded by the USA Environmental Protection Agency, enrolled three cohorts of the MOMS contaminant evaluation study [26]. MOMS was designed to observe the levels and effects of heavy metals, Persistent Organic Pollutants, and other anthropogenic pollutants in mothers and their infants residing in the YK Delta.…”
Section: Maternal Organics Monitoring Study (Moms) Methodsmentioning
confidence: 99%
“…The Maternal Organics Monitoring study (MOMS) is a prospective, ongoing cohort study examining diet and pollutant factors among mothers and their children in the rural Yukon Kuskokwim Delta (YKD) region in southwestern Alaska. Aggregating levels of nutrients from subsistence foods in maternal blood, the study seeks to understand if overall benefits of subsistence diets outweigh risks of exposure to environmental pollutants (Anwar et al 2016). In the MOMS, 28% of maternal bloods drawn at prenatal visits and 91% of cord bloods had 25(OH)D levels that were insufficient (<50 nmol/L).…”
Section: Introductionmentioning
confidence: 99%